A cost‐effective approach to factor assay calibration using a truncated live calibration curve. (17th August 2019) - Guy, Susan; Sermon‐Cadd, Anne M.; Shepherd, Fiona M.; Kitchen, Steve; Bowyer, Annette E.
Abstract: Introduction: The measurements of clotting factor activities are usually performed using a one‐stage clotting assay (OSA) or chromogenic substrate assay (CSA). Advances in automated coagulation analysers have led to the utilization of stored calibration curves. There are sometimes substantial intervals between test calibration and analysis of samples. Variability in results can be influenced by calibrant and methodology. Several guidelines recommend calibration and patient samples be performed together in parallel; this incurs costs, but reliance on a stored calibration curve may lead to inaccuracy of results over time. Methods: We evaluated inclusion of a live truncated (3 point) calibration curve using calibrator plasma alongside test samples and compared results calculated against the stored calibration curves and live truncated calibration to assess the impact on precision and accuracy. The feasibility of this was tested on two hospital sites in the UK; OSA and CSA were performed on Sysmex CS5100 using Actin FS, SynthASil, Innovin, Biophen chromogenic VIII and Rossix chromogenic IX. Results: Results of two batches of IQC were compared for FII, FV, FVII, FX, FIX:C, FXI, FXII and OSA FVIII (FVIII:C1) and CSA FVIII:C (FVIII:CR) and FXI:C. By utilizing a live truncated calibration, precision improved with the most striking examples: FXII %CV 23.1% to 3.1% (site A) FXI 7.3% to 2.4% (site B). The improvement in other clotting factors was more modest. Conclusion: To the best of our knowledge, this is the first study that demonstrates that the use of a live truncated calibration curve will improve precision and accuracy.